A Discourse Analysis Of Introductions In English And Vietnamese Linguistics Papers - Lê Thị Thuận (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2025)
Based on the theories of discourse analysis, this thesis conducts a discourse analysis of introductions of English and Vietnamese linguistics papers in order to discover some typical discourse features and then find out the similarities and differences in terms of the layout, lexical choices, syntactic features and cohesive devices between introductions of linguistics papers in English and Vietnamese. The research was conducted based on the combination of the descriptive method and the contrastive one. Sixty samples of English introductions of linguistics papers (IELPs) and sixty samples of Vietnamese introductions of linguistics papers (IVLPs) were collected from the internet and magazines for five recent years from 2009 to 2013. The findings show that along with some similarities, there are a number of noticeable differences. In the terms of layout, IELPs and IVLPS consist of three moves: move 1- establishing a territory, move 2 – establishing a niche, and move 3- occupying the niche which base on a “Create A Research Space”, CARS model (Swales, 1990). However, the English introduction is quite different from the Vietnamese one. In terms of lexical choices, IELPs use the negative qualitifiers and contrast terms commonly while IVLPs use them less frequently. With regard to the syntactic features, the passive voice, tenses and rhetorical questions are investigated respectively. For the cohesive devices, the thesis studies both lexical cohesion and grammatical cohesion. It is hoped that the results of this study will serve as an access to a profound understanding of English and Vietnamese introductions in linguistics papers.